Modelling the impact of higher temperature on the phytoplankton of a boreal lake - Anita Pätynen; J. Alex Elliott; Petri Kiuru; Jouko Sarvala; Anne-Mari Ventelä; Roger I. Jones (FINNISH ENVIRONMENT INST, 2022)
We linked the models PROTECH and MyLake to test potential impacts of climate-changeinduced warming on the phytoplankton community of Pyhajarvi, a lake in southwest Finland. First, we calibrated the models for the present conditions, which revealed an apparent high significance of internal nutrient loading for Pyhajarvi. We then estimated the effect of two climate change scenarios on lake water temperatures and ice cover duration with MyLake. Finally, we used those outputs to drive PROTECH to predict the resultant phytoplankton community. It was evident that cyanobacteria will grow significantly better in warmer water, especially in the summer. Even if phosphorus and nitrogen loads to the lake remain the same and there is little change in the total chlorophyll a concentrations, a higher proportion of the phytoplankton community could be dominated by cyanobacteria. The model outputs provided no clear evidence that earlier ice break would advance the timing of the diatom spring bloom.